Promoting Your Department to High School Seniors - Jeremy H Sarachan (Academic Chairpersons Conference Proceedings, 2017)
Increasingly departments must take charge of their recruitment, but most academics are new to public relations and marketing. What are the best methods to reach high school students? Led by a media and communication chair, this discussion will revolve around best practices that are both affordable and easy to manage.
Keywords: marketing; recruitment; enrollment; media; promotion